A Study on the Effect of Personality on Advertisement Preference and Consumer Behaviour of Working and Non-working Women - Nilofer (Indian Journal of Marketing, 2004)
The term consumer behaviour refers to the behaviour that consumers display in searching for, purchasing, using, evaluating, and disposing of products and services that they expect will satisfy their needs. The study of consumer behaviour is the study of how individuals make decisions to spend their available resources (time, money, effort) on consumption related items. It includes the study of what they buy, why they buy it, when they buy it, where they buy it, how often they buy it and how often they use it. Many researchers have supported this concept as Thomas J Olney Morris B Holbrook and Rajeev Batra (1993) studied the consumer response to advertising and the results indicate the chain of effect from the contents of TV ads, through emotional reactions and attitude towards the advertisements to actual viewing behavior. Biehal Gabriel J Siephens Debra & Curboeleonara (1991) studied the attitude towards the advertisement and brand choice. The results support the presence of an independent effect of the attitude towards the advertisement on brand choice over and above the attitude towards the brand.